Investment volatility during red sea crisis: Study in Asean country - Agustina,; Caroline Barus, Andreani; Ulya Firza, Syafira; Halim, Fandi; Tiadoraria Br Ginting, Litka (Edelweiss Applied Science and Technology, 2024)
The objective of this research is to investigate the volatility of investment instruments, with the aim of providing the best model for predicting investment value. In this topic, the main concepts and theories that underpin the research are presented. Efficient market hypothesis and rational expectations theory stand out, providing a solid basis for understanding the context of the investigation. The methodology adopted for this research GARCH modelling to analysis investment instrument and the impact of its volatility. Data collection was carried out through yahoo finance website and investing website during red sea war event. The research identified optimal GARCH models for different indexes and assets: GARCH (1,1) for JCI, STI, SET, and Bitcoin, E-GARCH (1,1) for KLSE, PSE, and VSE, and GJR-GARCH (1,1) for Gold. It discussed volatility persistence and leverage effects during the Red Sea War, considering model sensitivities, geopolitical impacts, and research limitations. This research's practical and theoretical implications inform financial risk management, highlighting the importance of robust volatility modeling. The findings can enhance portfolio optimization and investment strategies during geopolitical instability. These insights underscore the need for sophisticated approaches to manage financial risks effectively. This research uses advanced GARCH models to analyze volatility during the Red Sea Crisis, revealing asset-specific behaviors under geopolitical stress. The findings improve financial risk management and investment strategies in unstable conditions, enhancing volatility predictions and professional practices.